KEPEMIMPINAN YANG MENYELAMATKAN: ANALISIS KONSEP KEPEMIMPINAN MONKEY D. LUFFY DALAM ANIME ONE PIECE ARC “MARINEFORD” DAN KONSEP KEPEMIMPINAN YESUS SEBAGAI SAHABAT - Lontoh, Andheralvi Isaiah; Manguju, Yudha Nugraha (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2023)
This article discusses the leadership that has been used by Christianity which is often still not carried out effectively and even provides distance with the existence of a hierarchy. Joas Adiprasetya's Philiarchy leadership and the leadership of Monkey D. Luffy in the "Marineford" arc provide an offer that can be used in egalitarian church ministry and saves one another. Using qualitative research methods and a literature study approach, this paper finds that the results of the analysis of these two leadership concepts provide a more relevant leadership model in Christian life.